(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: Some population-based studies conducted in Bangladesh at different time points have revealed an increasing trend of diabetes prevalence ranging from 1.5% to 3.8% in the rural communities. The diagnosis of diabetes mellitus must be made with care since it has far reaching medical and social consequences. A number of biochemical tests are used in association with clinical assessment both for the initial diagnosis of this condition and the long-term monitoring of patients. Glycated hemoglobin provides an accurate and objective measure of glycemic control over a period of weeks to months. This study was designed to find the status of glycemic control in diabetic patients. Materials and Methods: A total number of 60 diabetic patients of various duration from > 20 years were included in the study group and 40 non-diabetic individuals in the control group. Biochemical parameters fasting plasma glucose (FPG), 2 hours post-prandial plasma glucose (PPPG) and HbA1c were studied. All the data were analyzed by using SPSS (Statistical Product and Service Solutions) version 12.0 for Windows software with a 95% confidence limit. Results: In the study group with mean FPG 8.28 mmol/L and mean 2 hours PPPG 12.09 mmol/L and mean HbA1c was 7.41%. All the parameters showed significant difference between study group and control group. FPG, PPPG and HbA1c were all increased in diabetic patients when compared to that of control group. Conclusion: Glycemic control is impaired in diabetic patients. Longer duration of diabetes mellitus shows less glycemic control. DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i1.19 Chatt Maa Shi Hosp Med Coll J 2013; 12(1): 4-8